Trees and Crime in Bogota, Colombia: Is the link an ecosystem disservice or service? (2018)
There is a perception that increased forest cover and density in urban contexts is associated with increased criminality. But, this complex relationship between urban vegetation, crime, ecosystem services (ES) and disservices (ED), has been little studied in low and middle income countries. This study's aim was to statistically determine if specific structural and socioeconomic characteristics of urban treescapes were related to crime occurrence, considered an ED, in a major Latin American city. We used spatial and statistical analyses of a public tree inventory, homicide occurrence, and available geospatial data to analyze if urban treescape, demographic, and socioeconomic variables were related to the incidence of homicides in Neotropical Bogota, Colombia. First, a generalized linear model indicated that fewer homicides occurred in public treescapes with taller trees and higher tree density. In contrast, the amount of overall green space and average tree basal area were not significant predictors of homicide occurrence. Second, a geographically weighted regression model indicated that the inclusion of tree basal area rendered tree height insignificant, and that higher basal areas were associated with fewer homicides. Thus, both models indicated that increased tree density and size were actually associated with lower homicide occurrences. The amount of public green areas was however, not significantly related to homicide occurrence. Results indicate that in general, Bogota´s treescapes provided overall net ES as opposed to ED in terms of crime. Findings could be used to develop land use policies and management practices that increase the overall provision and demand for ES from urban forests. © 2018 Elsevier Ltd